Simultaneous expansion of 9, 10 boron-doped anthracene in longitudinal and lateral directions. Issue 5 (4th January 2019) - John, Alexandra; Kirschner, Sven; Fengel, Melina K.; Bolte, Michael; Lerner, Hans-Wolfram; Wagner, Matthias
Abstract : Key structural and optoelectronic features of 2, 3, 6, 7-tetraarylated diboraanthracenes were compared with those of corresponding singly and doubly ring-closed diboratetracenes and -pentacenes. Abstract : Doubly boron-doped anthracenes and pentacenes have been longitudinally and laterally expanded through annulation of thiophene or benzene rings. The obtained series of closely related compounds allowed an assessment of key structure–property relationships with a focus on optoelectronic characteristics. Most of the products are benchtop-stable blue emitters and capable of accepting two electrons in a reversible manner. The syntheses involved late-stage modifications through photocyclization or stepwise oxidative C–C coupling (DDQ/BF3 ·Et2 O) as well as cyclocondensation of ortho -disilylated or -diborylated aryl building blocks.